Cash crisis in newly public Internet-based firms: an empirical analysis - Mudambi, Ram; Treichel, Monica Zimmerman (Journal of Business Venturing, 2005)
This study examines why, even when financial resource constraints are significantly relaxed, some new ventures struggle to survive while others prosper. Using the data of approximately 200 new Internet ventures that went public during the years 1997 through 1999, we propose that the performance of new ventures is a function of pre-initial public offering (IPO) characteristics. We determined that firm-level characteristics, including top management team (TMT), financial position, networks, and location, are related to the performance of struggling new ventures. We found strong evidence of agency relationships, so that a substantial reduction in equity holdings by the entrepreneurial team is a strong signal of impending crisis. Interestingly, similar reductions by venture capital (VC) backers did not serve as a signal of crisis.